THE THYROID GLAND STATUS IN PATIENTS WITH ANKYLOSING SPONDYLITIS DURING STANDARD THERAPY AND BIOLOGICAL THERAPY - G. R. Akhunova; F. V. Valeeva; I. G. Salikhov (Klinicist)
Aim. To evaluate the condition of the thyroid gland in patients with ankylosing spondylitis (AS) during standard therapy and biologicaltherapy (infliximab).Subjects and methods. Twenty-six patients with AS were examined; some of them received biological therapy with infliximab, while the others took non-steroidal anti-inflammatory drugs. The structuralunctional state of thyroid gland was evaluated in all patients. The effect of therapy was evaluated by the ASAS criteria. The efficiency of therapy was evaluated 24 weeks after therapy.Results. In 15.2 % of patients with AS were diagnosed thyroid gland disorders. The level of anti-thyroid antibodies, thyroid stimulating hormone (thyroid function) were correlated with active AS (index BASDAI), and the level of anti-thyroid antibodies were correlated with Creactive protein and erythrocyte sedimentation rate, the intensity of pain in the joints, number of swollen joints and inflamed enthesis.Therapy with non-steroidal anti-inflammatory drug is not provided significant effect on the structural and functional state of the thyroidgland, contributing to a downward trend in the level of antibodies to thyroid peroxidase. Treatment with Infliximab reduced the levels ofantibodies to thyroid peroxidase, thyroid stimulating hormone. This treatment was more effective in improving the structural and functionalstate of the thyroid gland.Conclusions. Against the background of the therapy in patients with AS is marked improvement in thyroid function, reduction of antithyroid antibodies, accompanied by a decrease in activity and improvement of clinical and laboratory parameters of AS.